Aporte de sedimentos, nutrientes e microorganismos no Rio Portuguesa - Carnellosi, Cristiany Fosquiani (2007)
The goal of this research was to quantify the amount of liquid, the drop of sediments, nutrients and micro-organisms from Portuguesa river hydrografical basin, Piquiri tributary in Ubiratã/PR. The river basin has an area of 40,819 km2, and from this total 6% is inside the urban area and 94% in the rural area. It was analyzed the physical-chemical parameters, microbiologicals the amount of sediments and quantify of flow. Every datas was about the flow, the use and the soil occupied. The evaluated of water quality from the Portuguesa river trough the analysis of parameters physical-chemical and biologics; the dissolved oxygen, electrical conductivity, pH, water temperature, turbidity, color, total kjeldahl nitrogen, nitrate, nitrite, total phosphorus, total coliforms and thermotolerant coliforms and solids in suspension. There were chosen 3 points at Portuguesa river called P1, P2 and P3 to the realization of the cross-section. The collection was done between a couple of weeks, or with the meaning increase of the amount of liquid. The parameters physical-chemical were analyzed in agreement of metodology described by Standard Methods for the Examination of Water and Wastewater (APHA-AWWA-WEF, 1995) and the bacteriologicals parameters were studied trough the subtract method COLILERT (cellophanes). The results show us the water temperature had a fluctuation, could have being associated with the time and the period of the year when sample was done such as the soil accupation. There were relations between electric conduction and dissolved oxygen. The parameter pH was closed to the neutrality in the whole studied points. The electric conduction, color and turbidity had the relation with flow such as increase or decrease of it. The variable dissolved oxygen showed the degrees less than 5mg.L-1 in all points between 08/03/2007 and 03/04/2007, having a relation to the temperature and flow. In relation of variability from nutrients (total phosphorus, nitrite and nitrate) exception to total kjeldahl nitrogen, that doesn t have relation to the flow, the smaller values found were associated with smaller flow. About the total coliforms, the P1 showed the biggest concentration associated to the increase of flow. Thermotolerant coliforms, P2 and P3 showed the biggest concentration, these points are localized next to the urban area. The key-curve of solid flush in suspension and flow, bring up good correlation among the three monitored points, shows up the worth of flow and sediments obtained are about the flush of basic flow by inecessability to the control stages of rain. About the production of sediments trough the analysis of the solids values in suspension and the bigger flows. To help the future use of water from Portuguesa river, was compared the parameters analyzeds to the stabilished limits from resolution CONAMA 357/2005, to put them in the class and use. Some parameters set the Portuguesa river in class 2 and others in class 3.